2014
DOI: 10.3389/fphys.2014.00057
|View full text |Cite
|
Sign up to set email alerts
|

Genetic silencing of Nrf2 enhances X-ROS in dysferlin-deficient muscle

Abstract: Oxidative stress is a critical disease modifier in the muscular dystrophies. Recently, we discovered a pathway by which mechanical stretch activates NADPH Oxidase 2 (Nox2) dependent ROS generation (X-ROS). Our work in dystrophic skeletal muscle revealed that X-ROS is excessive in dystrophin-deficient (mdx) skeletal muscle and contributes to muscle injury susceptibility, a hallmark of the dystrophic process. We also observed widespread alterations in the expression of genes associated with the X-ROS pathway and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…Sustained high ROS levels or, accordingly, a depletion of antioxidant defence, such as glutathione, led to decreased MyoD expression and subsequently to impaired myogenesis in vitro [22,23]. Comparable effects were recently observed in skeletal muscles in vivo, where an impaired antioxidant stress defence, including Nrf2 and glutathione, led to higher ROS levels, functional deficits and histopathological alterations [24,25].…”
Section: Discussionmentioning
confidence: 98%
“…Sustained high ROS levels or, accordingly, a depletion of antioxidant defence, such as glutathione, led to decreased MyoD expression and subsequently to impaired myogenesis in vitro [22,23]. Comparable effects were recently observed in skeletal muscles in vivo, where an impaired antioxidant stress defence, including Nrf2 and glutathione, led to higher ROS levels, functional deficits and histopathological alterations [24,25].…”
Section: Discussionmentioning
confidence: 98%
“…dysferlin) are mutated (Kombairaju et al . ). Nox2 also appears hyper‐sensitive and up‐regulated in skeletal muscle during mechanical unloading (Lawler et al .…”
Section: Introductionmentioning
confidence: 97%
“…34,40,41 Nrf2 protects against muscle atrophy due to denervation, aging, and inflammation and is a potential target for skeletal muscle disease. [42][43][44] While butyrate had no effect on mitochondrial ROS production induced by nerve injury, it did increase MnSOD and catalase activity, resulting in reduced oxidative damage. How HDACs regulate antioxidant enzymes is not known; a recent study found that a class I-specific HDAC inhibitor induces MnSOD and catalase after cardiac ischemia, 41 suggesting butyrate modulates oxidative stress by inhibiting class I HDAC.…”
Section: Discussionmentioning
confidence: 98%
“…Of interest, several studies have shown that HDAC inhibition activates the nuclear factor (erythroid‐derived 2)‐like 2 (Nrf2) antioxidant response pathway . Nrf2 protects against muscle atrophy due to denervation, aging, and inflammation and is a potential target for skeletal muscle disease . While butyrate had no effect on mitochondrial ROS production induced by nerve injury, it did increase MnSOD and catalase activity, resulting in reduced oxidative damage.…”
Section: Discussionmentioning
confidence: 99%